It takes a ‘spark’. Exploring parent perception of long-term sports participation after a practitioner-led, peer-group sports intervention for ambulant, school-aged children with cerebral palsy - Georgina Clutterbuck; Mikaila Gent; Daniel Thomson (JSAMS Plus)
Background: Participation in sport improves health and wellbeing, however children with disabilities participate in less physical activity than their peers. Interventions provided by health professionals in real-world sports contexts (i.e., in groups at sports facilities) have been shown to be effective in the short-term, however, long-term effects have not been investigated. Aims: To explore parents’ perceptions of long-term sports participation after a practitioner-led, peer-group sports intervention (Sports Stars) for ambulant, school-aged children with cerebral palsy. Methods: Parents of children who attended Sports Stars two to three years earlier participated in interviews exploring intervention experience and ongoing sports participation. Children's pre-intervention sports activity and participation goals were reassessed with the Canadian Occupational Performance Measure (COPM). Results: Fourteen parents participated. All reported that Sports Stars was an effective intervention, with children's increased confidence reported as the most beneficial outcome. Since attending Sports Stars, children participated in a variety of sports, the most common being swimming and soccer. Most parents reported environmental factors as a barrier to ongoing sports participation.Statistically significant improvements in children's relevant sports-focussed activity and participation goals were demonstrated compared to pre-Sports Stars (COPM activity performance mean improvement (MI) ​= ​3.94, p ​= ​0.004, participation performance MI ​= ​4.88, p ​< ​0.001). When compared to post-Sports Stars, children maintained, or further improved, ratings of performance and satisfaction at 2–3 years follow-up. Conclusions: Parents of ambulant children who participated in a short term, practitioner-led, peer-group sports intervention perceived that Sports Stars was the catalyst for subsequent changes to their children's long-term sports participation. Trial registration: ACTRN12617000313336.